A divide and conquer approach for simulating an airport system. (2017) - Scala, Paolo; Mota, Miguel Mujica; Bock, Nico De
Airport capacity, expressed as the maximum number of air traffic movements that can be accommodated during a given period of time under given conditions, has become a hard constraint to air transportation, owing to the scarce amount of resources on the ground and restrictions in the airspace. Usually, the problem of capacity at airports is studied separating airspace operations from ground operations, but it is evident that the two areas are tied to each other. This work aims at developing a simulation model that takes into account both airspace and ground operations. The approach used is a divide and conquer approach, which allows the combination of four different models. The four models refer to the airside and airspace operations. This approach allows to evaluate the system from different angles depending on the scope of the study, the results show the analytic potential of this approach.